Advanced Interactive Mathematical Tasks (DLO) for Moodle - Marcen, Benjamin; Fošner, Maja; Knežević, Nevena (International Journal of Interactive Mobile Technologies (iJIM), 2022)
In this paper, we will present the reasons for the implementation of eLearning system and different most often used learning models. The focus will be on mathematics in Moodle (LMS-Learning Management System) and on the possibilities of its use. Especially in the construction of new advanced interactive tasks in the field of derivatives and integrals. The main goal is to motivate students, encourage them to overcome theirs difficulties through an auto-study, giving them more confidence and making students keen on Mathematics. In particular, the idea of doing e-mathematics exercises within Moodle as friendly as possible for all users lecturers and students - will be presented.